Itus, Auv, Te'ek (Past, Present, Future) - Stoffle, Richard W. (Bureau of Applied Anthropology, University of Arizona, 1995)
This report concludes the first four years (1992 -1995) of Southern Paiute involvement in the Glen Canyon Environmental Studies (GCES), a program initiated by the Bureau of Reclamation (BOR) in 1982. Southern Paiutes have conducted ethnographic research and participated in the Congressionally mandated Environmental Impact Study (EIS) of Glen Canyon Dam water release policies on natural and human-made resources found in the Colorado River Corridor. These ethnographic studies have taken place in what is called the Colorado River Corridor which extends 255 miles down stream from Glen Canyon Dam to the end of the free flowing river at Separation Canyon within the Grand Canyon National Park. They have concentrated on investigating the impacts of the Dam's water releases to Southern Paiute cultural resources. Since the Final EIS was published in March 1995, emphasis has been placed on what is called the Adaptive Management Program of the GCES and attention has shifted to monitoring the water release impacts.